Acute Intradialytic Cardiac Function and Inflammatory Cytokine Changes During High‐Efficiency Online Hemodiafiltration With Acetate‐Free and Standard Dialysis Solutions. Issue 3 (29th December 2014) - Tiranathanagul, Khajohn; Tangvoraphonkchai, Kamonwan; Srisawat, Nattachai; Susantitaphong, Paweena; Tungsanga, Kriang; Praditpornsilpa, Kearkiat; Eiam‐Ong, Somchai
Abstract Acetate in standard acetate‐containing bicarbonate (AC) dialysis fluid could induce peripheral vasodilatation, suppression of myocardial function, and inflammatory cytokine production, resulting in intradialytic hypotension in conventional hemodialysis (HD) patients. Online hemodiafiltration (HDF) provides superior hemodynamic stability over HD. The potentially additive hemodynamic benefits of the novel acetate‐free bicarbonate (AF) dialysis fluid in online HDF have never been explored before. The present randomized, double‐blind, crossover study was conducted in 22 online HDF patients to investigate the impact of AF dialysis fluid on hemodynamic and cytokine changes compared with AC dialysis fluid in online HDF. The results demonstrated the comparable changes of arterial pressure between AF and AC online HDF. During the study periods, the incidences of composite intradialytic hypotension and other adverse events were not different. The baseline and hourly changes of cardiac index, cardiac output, and peripheral vascular resistance during dialysis were comparable (P = 0.534, 0.199, and 0.641, respectively). The percent reductions of NT‐proBNP and cTnT were not significantly different (72.6 ± 12.3 vs. 72.6 ± 12.8%, P = 0.99 and 35.2 ± 12.8 vs. 36.7 ± 12.0%, P = 0.51). The changes of all pro‐inflammatory cytokines (IL‐2β, IL‐6, IL‐8, and TNF‐α) and anti‐inflammatory cytokine (IL‐10) during dialysis were comparable between both groups. In conclusion, AF dialysis solution does not offer additional hemodynamic benefit for stable online HDF patients. The hemodynamic stability provided by online HDF might protect the adverse effects of acetate.